2011
DOI: 10.1007/s10964-011-9705-z
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Acculturation Discrepancy, Perceived Parental Knowledge, Peer Deviance, and Adolescent Delinquency in Chinese Immigrant Families

Abstract: Parent–child acculturation discrepancy has been considered a risk factor for child maladjustment. The current study examined parent–child acculturation discrepancy as an ongoing risk factor for delinquency, through the mediating pathway of parental knowledge of the child’s daily experiences relating to contact with deviant peers. Participants were drawn from a longitudinal project with 4 years between data collection waves: 201 Chinese immigrant families participated at Wave 1 (123 girls and 78 boys) and 183 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
2
31
2
1
Order By: Relevance
“…In immigrant families, discrepancies often exist in parents’ and children’s language skills, social contacts, identifications, and values (Kwak, 2003). These parent-child differences may present significant impediments to positive adjustment among adolescents and their families (Unger, Ritt-Olson, Soto, & Baezconde-Garbanati, 2009; Wang, Kim, Anderson, Chen, & Yan, 2012). For example, acculturation gaps in language abilities can inhibit effective communication, rendering it more difficult to discuss sensitive emotional issues.…”
Section: Specificity Principle: Timementioning
confidence: 99%
“…In immigrant families, discrepancies often exist in parents’ and children’s language skills, social contacts, identifications, and values (Kwak, 2003). These parent-child differences may present significant impediments to positive adjustment among adolescents and their families (Unger, Ritt-Olson, Soto, & Baezconde-Garbanati, 2009; Wang, Kim, Anderson, Chen, & Yan, 2012). For example, acculturation gaps in language abilities can inhibit effective communication, rendering it more difficult to discuss sensitive emotional issues.…”
Section: Specificity Principle: Timementioning
confidence: 99%
“…The literature is remarkably consistent in that parental warmth is generally predictive of lower rates of externalizing problem behaviors (e.g., White & Renk, 2012). While developmental research has shown that problem behaviors in adolescence usually predicts externalizing behavior into adulthood (Dubow et al, 2008), longitudinal research also indicates that decreases in parental warmth predict increased levels of externalizing behaviors in adolescents (Wang, Kim, Anderson, Chen, & Yan, 2012). Although studies linking parental warmth to externalizing behavior are less common among ethnically diverse populations, similar effects of parental warmth on externalizing behaviors have been shown in Latino/a families (e.g.…”
Section: Parenting and Externalizing Problemsmentioning
confidence: 93%
“…Many times when families emigrate, the acculturation process does not occur the same for parents as it does for children. Parent and child discrepancy in acculturation can lead to risk factors of child maladjustment (Wang, Kim, Anderson, & Chen, 2012). This discrepancy can create separation between parents and their children especially when children were left behind and rejoin their parents years later.…”
Section: Acculturative Stressmentioning
confidence: 99%